PEMBUATAN GAME TOWER DEFENSE MENGGUNAKAN ALGORITMA A* - Aloysius Wiranata; Budi Hartanto; Marcellinus Ferdinand Suciadi (CALYPTRA, 2018)
Nowadays, tower defense games doesn’t give its players freedom which they cannot create their own path, therefore a desktop based game of tower defense game which able to give its player freedom in creating their own path is created. This game is built using unity and can be played in single player. In this game, there is an objective that must be protected by its player. There will also be monsters that will try to find their own path to the objective. This monster will be using A* path finding algorithm. A* path finding algorithm is the most common path finding algorithm used in many games. This final project will be using A* algorithm library implemented by Aron Granberg. The using of this library is based on its clear documentation and easiness of using this library. From the result of analysis, the game will also have feature to create Custom Tower. Custom Tower is a feature that enables its player to modify attributes of a tower according to his own needs. In order to remain exciting and no tower is toooverpowered, the higher the attribute of a custom tower then the cost of building that tower will also be higher. From the game test results obtained that the presence of custom tower and custom track increases the enjoyment of playing tower defense game. Suggestions that can be given for further development is to add more variety of monsters and tower and multiplayer feature.